Assessing the impact of intermittent fasting and a lowcarbohydrate- high-protein diet on metabolic health and pancreatic histopathology in type 2 diabetic rat model - Alqusayer, Arwa M.; Ahmed, Waheeba E.; Althwab, Sami A.; Hamad, Essam M. (International Journal of Health Sciences, 2025)
Objective: The current study was conducted to investigate the effect of intermittent fasting (IF) with a low-carbohydrate-high-protein (LCHP) diet on blood glucose control in streptozotocin (STZ)-nicotinamide-induced type 2 diabetic rats (DR). Methods: Thirty male Wistar rats were divided into six groups (n = 5) including a group of normal rats (NR) that received a control diet (CD) (50% carbohydrates, 17% protein, and 33% fat) with ad libitum (AL) feeding. The remaining 5 groups were DR injected with STZ and fed on CD or LCHP diet (40% carbohydrates, 30% protein, and 30% fat) for 6 weeks, either AL or IF (with a time-restricted feeding of 16 h followed by 8 h feeding period). There was a standard control group treated with metformin and fed on CD with AL feeding. A random blood glucose was measured. Changes in body weight and feed intake (FI) were monitored weekly. Results: Feeding rats on LCHP and IF and their combination significantly reduced FI, body weight gain, blood glucose (P < 0.001), and improved insulin resistance (P <0.05) with no effect on the insulin levels (P > 0.05). LCHP and IF decreased the levels of triglycerides and very-low-density lipoprotein and showed a possible protection against atherosclerosis by reducing the atherogenic index (P < 0.01). Furthermore, LCHP+IF greatly alleviates the pancreatic histopathological changes induced by STZ and showed the normal histological structure of the Langerhans islets. Conclusion: IF with a LCHP diet could be effectively used in improving the indicators of glucose control, and reversing pancreatic histopathological alterations in type 2 diabetes.